Feminisierung als Statusproblem: Der Verein Deutscher Chemiker und seine Berufskonstruktion der Chemikerin - Horstmann, Anna (Österreichische Zeitschrift für Geschichtswissenschaften, 2023)
This article traces the gender discourse in the German chemical industry at the beginning of the twentieth century based on the public discussion of the association Verein Deutscher Chemiker (Association of German Chemists) in the association’s journal Zeitschrift für Angewandte Chemie. Methodologically, the analysis builds on the work of Ulrike Teubner and Angelika Wetterer on gender constructions in work processes, and examines the discourse of the Association with regard to the construction mechanisms of gender and how these were used to develop job profiles and gender-segregated fields of activity. The article focuses on the linkage between status concerns and the fear of the feminization of the profession, which was at the centre of this debate.